Uridine/UMP metabolism and their function on the gut in segregated early weaned piglets. Issue 7 (24th June 2019) - Li, Guanya; Xie, Chunyan; Wang, Qinhua; Wan, Dan; Zhang, Yan; Wu, Xin; Yin, Yulong
Abstract : Uridine monophosphate (UMP) is a major nucleotide analogue in mammalian milk and uridine (UR) is its gastro-intestinal metabolite in vivo . Abstract : Uridine monophosphate (UMP) is a major nucleotide analogue in mammalian milk and uridine (UR) is its gastro-intestinal metabolite in vivo . This study aims to investigate the functional effects of UMP and UR on the gut in vitro and in vivo . Twenty-one piglets were randomly allotted into three groups, the control group, UMP group and UR group, and orally administered UMP or UR for 10 days. Results showed that UMP and UR supplements improved the ADG of piglets, and decreased the diarrhea rate. UR increased the jejunum villus length/crypt depth ratio, Claudin-3 and E-cadherin expression, and the pyrimidine nucleotide metabolic enzymes including CMPK1, RRM2, UPRT, CTPS1 and CTPS2 in the duodenal mucosa. Both the UMP and UR decreased the expression of CAD and RRM2 at the jejunal mucosa. Moreover, UMP and UR increased the apoptosis ratio of intestinal epithelial cells in in vivo and in vitro experiments. Taken together, oral administration of UR and UMP could improve the small intestinal morphology, promote epithelial cell apoptosis and renewal of intestinal villus tips, and benefit intestinal development and health thus improving the growth performance and reducing the risk of diarrhea in early-weaned piglets.